Shared decision-making in oncology: preferences in older versus younger patients of an oncology clinic : a conjoint analysis - Gaster, Corinna; Hofheinz, Ralf-Dieter; Burkhardt, Heinrich (Oncology research and treatment, 2021)
Background: Data concerning older patients’ preferences with regard to physician-patient interaction and the concept of shared decision-making (SDM) in oncology are still sparse although significantly influencing treatment planning. Methods: Patients were recruited as a convenience sample from an outpatient oncology department. To test for patients’ attitudes toward participating in clinical decisions, the PEF-FB-9 questionnaire (the German version of SDM-Q9) and the autonomy preference index (API) instrument were applied. A conjoint analysis was performed by a full set of vignettes exposing three different clinical attributes: clinical experience in oncology of the responsible physician, type of hospital, and type of physician-patient interaction in decision-making. Two independent cohorts were retrieved: patients aged <65 years and patients aged >70 years. Results: A total of 71 patients were included. Younger subjects rated higher (44 vs. 10, p < 0.001) on the API scale. In both cohorts, physician-patient interaction received the highest preference values compared with type of hospital and physician experience. Analysis for age differences on preference values showed significantly higher values among the older patients concerning physician-patient interaction and lower values concerning type of hospital. Further analysis of the preferred type of physician-patient interaction revealed the highest preference in both cohorts for SDM. Conclusions: The high significance of physician-patient interaction could be proved. As a SDM approach is preferred in older and younger patients, an age-related different approach does not seem appropriate.
Gesehen am 29.04.2021